Legal Consequences of the Separation of the Chagos Archipelago from Mauritius in 1965 (I.C.J.). (June 2019) - Allen, Stephen
Abstract : In its Chagos Advisory Opinion, the International Court of Justice (ICJ) addressed two questions posed in a request from the UN General Assembly. First, had Mauritius's decolonization been completed when it gained independence in 1968, after the excision of the Chagos Archipelago? Second, what were the legal consequences flowing from the United Kingdom's continued administration of the Archipelago? It was thought that the Court might shy away from giving an Opinion in this case as, arguably, it concerned a bilateral sovereignty dispute that the United Kingdom had not agreed to have resolved by judicial decision. However, as it turned out, the Court delivered surprisingly robust responses to the questions posed. The Opinion—and the numerous Separate Opinions that accompanied it—offer a thorough re-evaluation of the customary international law (CIL) concerning the right to self-determination in cases of decolonization.